ROBOTIC ARMS MOVEMENT USING ELECTROENCEPALOGRAM (EEG) - ABD FATAH, WAHYU HIDAYAT (Universiti Teknologi Petronas, 2013)
To achieve the goal for this project, the spreads sheet had been use as a guide for this goal project using brain wave to control robotic arms. In recent years, EEG had been use to analyze of human brain wave such as medical diagnosis purpose. The information about human brain from medical and brain wave analysis had been use for development of this project. The system that been create in this project is been made to use our brain wave to move the robotic arm. In order to done this project, the EEG device and Matlab processing is used. EEG is used to locate the brain wave changes alpha and beta in the occipital, brain lobe. Meanwhile, Matlab is coding to analyze the brain wave and give order to robotic arms to move in any direction.